Environmental technical texts for linguists and translators: the case of the environmental audit report (Italian-Spanish) - González Vallejo, Rubén (2024)
The environment covers many fields of knowledge, and the evolution of its knowledge is increasingly present in the news and in scientific research. It also includes texts from all the sciences it encompasses, and the cognitive and social framework of these genres favours an automatic context and the appearance of hybrid genres resulting from the crossing of disciplines. For this reason, this article deals with the scientific and technical language of the environment and presents a classification of technical textual genres, with special attention to the technical genre of the environmental audit report, both in Spanish and Italian. Specifically, the environmental audit report turns out to be a scientific and technical document, since the presentation of data, the result of scientific research, is followed by the application of techniques with certain measuring devices for the collection of data, as a preliminary step to the integration of results. For its analysis, a brief study based on a microcorpus of environmental audit reports in both languages will be presented, with the aim of exploring new horizons for linguists and translators in the environmental field and thus filling the gaps still existing in the Italian-Spanish language pair.